2022
DOI: 10.3390/agriculture12040474
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies Determination Effectiveness for the Productivity of Organic Winter Wheat Production in Low Soil Performance Indicator

Abstract: The most important aspect of precision farming is the prediction of crop yield and quality. Digital technologies (soil maps and combine harvester with telemetry functions) were used to determinate the yield of organically grown winter wheat (variety Skagen) in two fields of 18.8 and 4.5 ha in Lithuanian regional conditions, in an area classified as low-performance for farming. The objective of the research was to determine the effectiveness of digital technologies (soil maps and combine harvester with telemetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Information on soil typology and texture at 1:10000 scale in Lithuania can be found on the website www.zis.lt, and growers can use smart harvesters to obtain data in the yield of crops grown in the field, or use field sites to determine the yield of the crops grown in the field, as was done during current experiment. Research data is also available in scientific and methodological publications (Budňáková, Čermák, 2009;Peralta et al, 2015;Staugaitis, Vaišvila, 2019;Astrauskas, Staugaitis, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on soil typology and texture at 1:10000 scale in Lithuania can be found on the website www.zis.lt, and growers can use smart harvesters to obtain data in the yield of crops grown in the field, or use field sites to determine the yield of the crops grown in the field, as was done during current experiment. Research data is also available in scientific and methodological publications (Budňáková, Čermák, 2009;Peralta et al, 2015;Staugaitis, Vaišvila, 2019;Astrauskas, Staugaitis, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the experiments showed that different topography and variability of soil properties are important for sustainable management system, crop productivity, and land use planning (Staugaitis, Šumskis, 2011;Juhos et al, 2015;Žičkienė, 2016;Astrauskas, Staugaitis, 2022). Other researchers have found that soil type and its ability to accumulate moisture are very important for the fertility of winter wheat (He et al, 2014).…”
Section: Introductionmentioning
confidence: 98%